Impact of protein reinforcement on the deformation of soft cereal foods under chewing conditions studied by X-ray tomography and finite element modelling. (December 2020) - Assad-Bustillos, M.; Guessasma, S.; Réguerre, A.L.; Della Valle, G.
Abstract: The mechanical properties of sponge cake (SC) and brioche (B), and their pulse protein fortified version (FSC and FB) have been characterized under compression (>90% in height reduction); during recording the evolution of their cellular structure was recorded using high resolution X-ray tomography. Due to protein reinforcement, FB had smaller gas cells and slightly larger cell walls than B, whereas FSC had only smaller cells than SC. The four products displayed non-linear mechanical behavior, with plastic deformation in the case of brioches. Results showed that sponge cakes, having thinner cell walls, exhibited premature fracture, while brioches, characterized by thicker cell walls, buckled, making the food sample more difficult to form fragments. Three dimensional Finite Element models were implemented based on the X-Ray micro-tomography 3D images. Results have shown that brioches, and particularly FB, displayed less efficient stress transfer, and thus were less prone to fragmentation. By comparison with results previously obtained on real food boluses, these results allowed understanding the mechanisms that govern food fragmentation during chewing and underlined the importance of the cellular structure of these cereal foods. Highlights: 3D images from X-ray micro-tomography show that sponge-cake fracture occurs early. FEM shows that brioche needs higher levels of stress than sponge-cake to fragment. Protein fortification impacts cellular structure more than mechanical properties. Thicker cell walls, like in brioche, will deform more easily, thus reducing fracture. Results explain differences in the food oral processing of these soft cereal foods.